PERKEMBANGAN DAN PENANAMAN NILAI AGAMA PADA MASA REMAJA - Ahmad Fahrurrozi (An-Nahdlah: Jurnal Pendidikan Islam, 2022)
Abstract:This study aims to determine how the development and cultivation of religious values ​​in adolescence. This study uses a library research method, namely the library study by collecting related documents regarding the research theme in the form of books, articles, and others. Adolescence is often a mental shock so that children do something based on what they like, regardless of violation or not religious and cultural norms. Therefore, the planting of religious values ​​needs to be done early on. As for the results of this study, adolescents experience cognitive development, physical-motor development, socio-emotional development, and sexual development. Efforts can be made to inculcate religious values, namely there are seven ways: parents and teachers foster interest in religion, parents and teachers carry out religious activities in an interesting way, parents and teachers train teenagers to do positive things, parents and teachers are role models Good parents and teachers always pay attention to children first regarding religious values, parents and teachers pay attention to who children are friends with, and parents and teachers provide teaching about good ethics and morals. Keywords:Development, Religious Values, and Adolescence